TRUECRYPT SEBAGAI ALAT BANTU YANG EFEKTIF UNTUK PENYIMPANAN DOKUMEN MENGGUNAKAN PERANGKAT YANG TERENKRIPSI - Sucipto Adisuwiryo (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
The document is one of the outputs of an activity both individuals and organizations. With thepassage of time and the increasing activity of the resulting document will be many more. The resultingdocuments exist that are not confidential, but there is also a secret document in which those who do nothave the right authorization or permission is forbidden to access the document. The more secretdocuments to be protected, the more inefficient when any protected documents one by one. Hence theneed is being protected storage devices such documents, not the documents.TrueCrypt is a software that can be used to create an encrypted document storage device that canbe stored either in the hard disk or USB flash disk. Document storage device capacity can vary rangingfrom kilobytes (KB) to the units of gigabytes (GB). In addition, TrueCrypt can be mounted either on theMicrosoft Windows operating system, Mac OS X, and Linux. Encryption and decryption process fordocument storage devices will be done automatically before loading and storage process with no userintervention. To protect your document storage device with TrueCrypt can use a password only or acombination of passwords and key-file.TrueCrypt can be used to decrypt the document storage device with more than one format (FATand NTFS) simultaneously. Two or more document storage device that has been created can be decryptedon a different drive so that all storage devices such documents can be used like any other storage devicedocuments. After the document storage device didekripsikan or op